Editorial - James, Leena (Ushus Journal of Business Management, 2021)
On behalf of the editorial team, I have great pleasure in presenting to you this issue of ’Ushus’ with a new look and feel. The tenth issue of ’Ushus’ is a gratifying watershed for all of us who launched the journal in 2002 and completed the ten consecutive issues successfully. Innovation and creativity are always at the top of the corporate and institutional agenda. Never a fad, but always in or out of fashion, innovations and creativity get rediscovered as a growth enabler. Each generation embarks on the same enthusiastic quest for newer things and faces the same challenge of overcoming innovation stifles.